The Properties of Normal Concrete with Ground Manganese Slag as Binder Replacement - Ng, Chee Khoon; Johnson Ting, Kwong Sen; Nichole Louise, Jack; Leonard Lim, Lik Pueh; Ting, Sim Nee (Semarak Ilmu Publishing, 2024)
Manganese slag is a by-product from the production of ferrosilicon and manganese alloys. It has been found to possess pozzolanic properties and is therefore suitable for use in concrete mixtures. This paper investigates the properties of normal concrete with ground manganese slag as a binder replacement in terms of workability, compressive strength, flexural strength, and leaching characteristics. In this study, it is found that using ground manganese slag as a binder replacement increases the slump of fresh concrete. It is also found that using ground manganese slag as a binder replacement reduces both the development of compressive and flexural strengths. However, at a 10% binder replacement rate, the deterioration is considered minimal. The results of leaching characteristics from 'The Tank Test' show that using ground manganese slag as a binder replacement increases the alkalinity of the solution surrounding the concrete, indicating that the metal ions in the ground manganese have diffused and dissolved in the solution.